Pengaruh Kualitas Audit, Debt Default, dan Financial Distress terhadap Opini Audit Going Concern : (Studi Empiris pada Perusahaan Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Ajeng Putri Wahyuningtyas; Beti Nurbaiti; Endah Prewesti Ningrum; Tutty Nuryati; Tri Yulaeli (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research aims to examine the influence of audit quality, debt default and financial distress on going concern audit opinions. The population in this research are Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange in 2020 - 2023. The sampling technique used was the purposive sampling method. The population in this study was 78 companies with 312 observations. This research was measured using SPSS 23 and tests were carried out, namely descriptive statistical analysis, classic assumption tests, namely multicollinearity tests, binomial logistic regression tests (overall model fit, goodness of fit and coefficient of determination or R2), hypothesis tests (partial tests and simultaneous tests). The results of this research show that audit quality has a negative effect on going concern audit opinion, debt default has a positive effect on going concern audit opinion, financial distress has no effect on going concern audit opinion.